(untitled) - Hayashi, Shūji (Tokyo, 1988)
Author of the book shows how traditional attitudes and beliefs about time, space and interpersonal relations affect the way business decisions are made in Japan. These beliefs and attitudes are contrasted with those of the Western world and neighboring societies (Korean and Taiwanese, primarily). The book shows clear differences in responses to ethical problems and practical solutions.
Keywords: Quản trị công nghiệp,Industrial management; Khía cạnh xã hội,Social aspects; Nhật Bản,Japan